(untitled) (Texas Journal of Philology, Culture and History, 2023)
In the article, morphology is formed as a branch of descriptive grammar in the traditions of ancient (antique) linguistics, views on the cases of opposition (substance and accident relationship), analogy (similarity) and anomaly (departure from similarity, deviation from the norm) of the base form of the word and the units added to it were presented. The traditional classification of word groups and grammatical categories took place in later linguistic studies. The European Renaissance (from the 14th century onwards) also led to the emergence of special terms related to word structure.